Assessing the Public’s Social Acceptance of Renewable Energy Management in Taiwan - Hsing-Chih Chen; Chun-Hung Lee; Timothy Bernd Wallace Seekings; Linh Bao Nguyen (Land)
Renewable energy (RE) is one of the keys to achieving the global goal of net-zero carbon emissions by 2050. Understanding the factors influencing public participation behavior and social acceptance in RE management (REM) is thus essential to a sustainable energy transition embraced by communities and stakeholders. This study aims to assess nine indicators in REM across three dimensions of social acceptance through the public lens, employing an importance–performance analysis. Our findings reveal a significant gap between the perceived importance and performance of various REM components, suggesting dissatisfaction among respondents. Furthermore, the highest priority for improvement was given to the following strategies: “strengthening communication with residents”, “reducing air pollution emissions from power plants”, “establishing supervision and management mechanisms”, and “building smart grid and power storage equipment” to ensure successful implementation of REM policies. We also found that respondents who were under 50 years of age, lived in northern Taiwan, had a higher monthly income, and had a better awareness of social acceptance were more likely to participate in the energy transition. The insights gained from this study outline policy implications for improving the public’s social acceptance and advancing the development of RE in Taiwan, contributing to the world’s carbon-neutral mission.